Collaboration of Pharmacy, Laboratory, Nursing, Radiology, Healthcare Administration, Health Security, Physiotherapy, and Administration Departments to Enhance Healthcare Quality and patient safety in Saudi Arabia - Dighriri, Ibrahim Mohammed; Alruwaili, Bedour Mohammed; Alyami, Hadi Saleh Yahya; Alyami, Hussain Saleh Yahya; Alyami, Faris Saleh Hadi; Alanazi, Abdulmajeed Azzam; Alfuhigi, Mubarak Mussad; Halawani, Juwiriyyaah M Abdulwahab; Alzahrani, Sameer Mosa; Mulla, Rajeh Ali; Alhindi, Rami Suood; Munaggil, Bassam Abdulfatah; et al. (Journal of Ecohumanism, 2024)
The healthcare system in Saudi Arabia has undergone a significant transformation toward an integrated, collaborative approach to healthcare delivery, driven by the ambitious goals of Saudi Vision 2030 and the National Transformation Program in Healthcare. This review investigates and analyzes practical collaborations between various departments, including Pharmacy, Laboratory, Nursing, Radiology, Healthcare Administration, Health Security, Physiotherapy, and Administration in Saudi healthcare institutions to enhance quality and patient safety. By examining organizational structures, department-specific roles and interdepartmental interactions, this study highlights how coordinated efforts between these departments contribute to improved patient outcomes and healthcare delivery efficiency. The analysis revealed successful collaboration depends on clear communication channels, standardized operating procedures, and integrated information systems that facilitate real-time data sharing across departments. While challenges exist, including organizational hierarchies, technical integration issues, and communication barriers, opportunities for improvement through technological advancement, professional development initiatives, and refined policy frameworks show promise for future development. The findings emphasize that interdepartmental collaboration is essential for achieving the quality healthcare goals outlined in Saudi Vision 2030, particularly emphasizing patient safety, resource optimization, and service excellence. This review provides valuable insights into the current state of healthcare collaboration in Saudi Arabia and offers recommendations for enhancing interdepartmental coordination to advance healthcare delivery in the country.